DILEMA KEPAILITAN DI TENGAH SITUASI PANDEMI COVID 19 SEBAGAI AKIBAT MARAKNYA KREDIT BERMASALAH DI INDUSTRI JASA KEUANGAN (Lex Jurnalica, 2021)
AbstractThe COVID-19 pandemic that has existed since the beginning of 2020 has had a negative growth effect on economic life as a result of the limitation of community activities with the Large-Scale Social Restriction (PSBB) scheme, the implementation of Emergency Community Activity Restrictions (PKMM Emergency) to the imposition of Restrictions on Community Activities. 1, 2, 3 & 4 (PKMM level 1,2,3 & 4). Restrictions in the form of social distancing, closure of business activities, services & entertainment will certainly have a negative impact on the business sector which is included in the non-essential category in handling the COVID-19 pandemic, such as the provision of basic necessities, hospitals, banks, pharmacies and others. Non-essential businesses of course cannot move freely as in the period before the COVID-19 Pandemic, so that it leads to paralysis of business activities and has an impact on increasing non-performing loans in the financial services sector. This of course has the potential for many industries that can be sued for bankruptcy in accordance with the provisions of the Law of the Republic of Indonesia number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Bankruptcy lawsuits which have the potential to affect many industries, of course, directly or indirectly cause disruption of business activities and the loss of livelihoods of millions of workers if the Government does not anticipate the negative effects that may arise from the Law of the Republic of Indonesia number 37 of 2004 concerning Bankruptcy and Suspension of Liability Debt Payment.Keywords: Pandemic, bankruptcy, creditAbstrakPandemi COVID 19 yang telah ada sejak awal tahun 2020 telah membawa pengaruh pertumbuhan negatif terhadap kehidupan perekonomian sebagai akibat dari dibatasi nya aktivitas masyarakat dengan skema Pembatasan Sosial Berskala Besar (PSBB) , Pemberlakuan Pembatasan Kegiatan Masyarakat Darurat ( PKMM Darurat) hingga Pemberlakukan Pembatasan Kegiatan Masyarakat level 1, 2, 3 & 4 ( PKMM level 1,2,3 & 4). Pembatasan yang berupa jaga jarak, penutupan kegiatan bisnis , jasa & hiburan tentu nya berdampak buruk terhadap sektor usaha yang masuk dalam kategori bukan bersifat esensial dalam penanganan pandemic COVID 19 seperti penyediaan bahan sembako, rumah sakit, perbankan , apotik dan lain lain. Bisnis yang bersifat Non Esensial tentunya tidak dapat beraktivitas dengan leluasa seperti pada masa sebelum Pandemi COVID 19 , sehingga bermuara terhadap lumpuhnya kegiatan usaha serta berdampak pada kredit bermasalah yang meningkat di sektor jasa keuangan. Hal ini tentunya berpotensi pada banyaknya industri yang dapat digugat pailit sesuai ketentuan pada Undang Undang Republik Indonesia nomor 37 tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. Gugatan Kepailitan yang berpotensi akan banyak menimpa berbagai industri tentunya secara langsung atau tidak langsung menyebabkan terganggunya aktivitas bisnis serta hilangnya mata pencaharian jutaan tenaga kerja apabila Pemerintah tidak mengantisipasi efek negatif yang dapat timbul dari Undang-Undang Republik Indonesia nomor 37 tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang.Kata kunci : Pandemi, kepailitan, kredit